2022
DOI: 10.2196/34874
|View full text |Cite
|
Sign up to set email alerts
|

Global Pattern and Trends in Penile Cancer Incidence: Population-Based Study

Abstract: Background Penile cancer is a relatively rare genital malignancy whose incidence and mortality are rising in many countries. Objective This study aims to assess the recent incidence and mortality patterns and incidence trends of penile cancer. Methods The age-standardized incidence and mortality rates (ASIR and ASMR, respectively) of penile cancer in 2020 were estimated from the Global Cancer Registries (GLO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 74 publications
0
30
0
1
Order By: Relevance
“…Only the admission rate for penile cancer demonstrated an increasing trend, although it was not significant across the study period. Surely, the incidence of penile cancer is increasing in many countries in recent years [ 25 ] and, despite the lack of significant results, it can heavily impact the healthcare system in the Abruzzo region, and a preventive strategy should be implemented. The results of this study highlight how the greatest decreases in admission rates were reported for genital warts, cervical cancer, and anal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Only the admission rate for penile cancer demonstrated an increasing trend, although it was not significant across the study period. Surely, the incidence of penile cancer is increasing in many countries in recent years [ 25 ] and, despite the lack of significant results, it can heavily impact the healthcare system in the Abruzzo region, and a preventive strategy should be implemented. The results of this study highlight how the greatest decreases in admission rates were reported for genital warts, cervical cancer, and anal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, in some countries such as India or Brazil, the prevalence is high ranging from 2.3-8.3 per 100,000 person-year ( 2-4 ). In Thailand, according to data from 2008-2012, the age-standardized rate of penile cancer incidence is high (1.4 per 100,000) and ranked top three in the world ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Penile cancer is an uncommon form of malignancy, with an estimated incidence of 0.8 cases per 100,000 men globally in 2020. 1 It is typically diagnosed in older men, with the majority of cases occurring in men over the age of 60. 2 Squamous cell carcinoma (SCC) is the most common histopathology and is responsible for 95% of all cases.…”
Section: Introductionmentioning
confidence: 99%